Existence of Physical Solutions to the Boundary Value Problem of an Equation in Modeling Oil Film Spreading Over a Solid Surface (Journal of Partial Differential Equations, 2020)
A boundary vaJue problem to a fourth order nonlinear degeneraw para-holic equation arising in modeling oil film spreading over a solid surface is studied in the present paper. Basing on the consideration of physical phenomenon describrd by the original model, the authors forcus mainly on the case of two-dimensional space. The existence of nonnegative and radial solutions is established for nonnegative initial datum.